Hubungan antara Internal Locus of Control dengan Minat Berwirausaha Alumni Pelatihan Bordir di LKP Muslimah Group - Anggun Kurnia Sari; Wirdatul Aini; Jalius Jalius (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
This research is motivated by the low interest of entrepreneurship of alumni of embroidery training at Lembaga Kursus Pelatihan (LKP) Muslimah Group of Solok City. This is allegedly due to lack of internal locus of control of embroidery alumni training. The purpose of this study is to describe (1) internal locus of control of embroidery alumni training, (2) interest in entrepreneurship of embroidery training alumni, and (3) relationship between internal locus of control with interest in entrepreneurship of embroidery training alumni. This type of research is correlational quantitative research. The population in this study amounted to 60 people and a sample of 30 people. The sampling technique uses cluster random sampling. Data collection techniques in this study in the form of questionnaires, while data collection tools using questionnaires. Data analysis techniques using the formula percentage and product moment. The result of research shows that: (1) Locus of internal control of embroidery alumni is still low, (2) Interest in entrepreneurship of alumni of low embroidery training, and (3) There is a significant relationship between internal locus of control with entrepreneurship interest alumni embroidery training in LKP Muslimah Solok City Group.